2013
DOI: 10.1149/2.007306jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Carbon Black to a Porous Zinc Anode in a Zinc-Air Battery

Abstract: Zinc-air batteries were fabricated using porous zinc anodes with various concentrations of Super P carbon black additive. The introduction of Super P significantly improved the electrochemical performance of the batteries. The specific discharge capacity and power density of the Zn anode with 2 wt% Super P anode was 776 mA h g−1 and 20 mW cm−2, respectively. The batteries also exhibited good durability and stability at an open circuit voltage maintained at approximately 1.4 V. The bridging between Zn powders b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…There was about a 60% improvement of peak power density over BZn. The highest specific power density at room temperature achieved by Masri and coworkers [25] was 20 mW cm − 2 by using zinc powder mixed with 2 wt% Super P as the anode and MnOx-based air electrode as the cathode. This results indicated that the anode prepared by pulse plating with frequency of 500 Hz revealed a 15% improvement in power density without temperature effect.…”
Section: The Influence Of Anode Characteristics On Discharge Performancementioning
confidence: 97%
“…There was about a 60% improvement of peak power density over BZn. The highest specific power density at room temperature achieved by Masri and coworkers [25] was 20 mW cm − 2 by using zinc powder mixed with 2 wt% Super P as the anode and MnOx-based air electrode as the cathode. This results indicated that the anode prepared by pulse plating with frequency of 500 Hz revealed a 15% improvement in power density without temperature effect.…”
Section: The Influence Of Anode Characteristics On Discharge Performancementioning
confidence: 97%
“…Electrode structural additives, such as acetylene black, graphite, activated carbon, carbon black and graphene oxide, are widely used in zinc-electrodes to inhibit the formation of dendrites. For example, Mohamad et al 96 added Super-P to a porous zinc-electrode and investigated the performance of the assembled RZABs in a 6 M KOH electrolyte. The obtained results indicated that the zinc-electrode with 2 wt% Super-P could give a specific discharge capacity of 776 mA h g À1 and a power density of 20 mW cm À2 , induced by the arrangement of zinc particles and Super-P powder on the porous zinc-electrode ( Fig.…”
Section: View Article Onlinementioning
confidence: 99%
“…Recently, zinc‐air batteries have attracted tremendous attention because of their strong potential for future energy applications,, ,, ;, . Zinc‐air batteries use raw materials which are relatively low cost, have low toxicity, and are environmentally friendly but exhibit high specific energy density.…”
Section: Introductionmentioning
confidence: 99%